Effectiveness of the Reading English Adapted Digests (READ) program in the acquisition of the English language in the students of the Linguistics and English career and the Language Institute of the Universidad Peruana Unión - Apaza Romero, Abel (2012)
This is a quantitative type research with a pre experimental design. It was carried out by) the students from the Linguistics and English career and the Language Institute of the Universidad Peruana Unión, in order to determine the effectiveness of the program "Reading English Adapted Digests" (R.E.A.D.) in the acquisition of the English Language. The analysis showed that there are significant differences in favor of the study groups of Linguistics and English career. The results allow us to validate the program and at the same time recommend it as a very important part in the teaching-learning process.